The Influence Of Prospective Students' Motivation To Determine Higher Education Using Analytical Hierarchy Process (Ahp) - Juliarta , Fresly (International Journal of Educational Research & Social Sciences, 2022)
This study aims to determine the motivational factors of Labuhanbatu University students in choosing a college. This research is an exploratory research through policy evaluation. The data analysis method used in this research is descriptive quantitative. The sampling technique used is multistage random sampling, according to Arikunto, which is 25% of the population. The data analysis technique used is the Analytical Hierarchy Process (AHP). From the data that the authors obtained, there are five motivational factors studied. The highest rank is related to motivational factors in determining tertiary institutions, namely achievement motivation factors with eigenvector value = 0.31, university image motivation factors with eigenvector = 0.25, motivational process factors with eigenvector = 0.20, educational zoning motivation factors with eigenvector = 0.14 and the motivation factor of alumni perception with eigenvector = 0.10. This shows that of the five motivational factors obtained, the most dominant motivational factor is achievement motivation (first rank) after completing his education. The second most dominant factor is the university's image. The image of a university greatly influences why students choose to continue to higher education here. Labuhanbatu University which is well accredited is a university that is targeted by prospective new students who want to continue their education at Labuhanbatu University.